2016
DOI: 10.1080/10496475.2016.1138269
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents and Cytotoxic Activity ofKhaya grandifoliolaandKhaya senegalensisFlower Extracts

Abstract: The volatiles obtained from fresh flowers of Khaya grandifoliola C.DC. and Khaya senegalensis A.Juss. by hydro-distillation method were analyzed by gas chromatography and gas chromatography-mass spectrometry. Sesquiterpenes represent 86.32% and 80.86% of the identified volatile compounds of K. grandifoliola (KgO) and K. senegalensis (KsO) oil, respectively. Caryophyllene-oxide (23.01%), isocaryophyllene (Z) (21.99%), and α-humulene (13.46%) were the main compounds identified in KgO, whereas in KsO they were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…These extracts are therefore considered non-toxic. Similar research by EL Souda et al [ 42 ] showed that the volatile extract of Khaya senegalensis had moderate cytotoxicity on MCF7 cells with a IC 50 of 79.7 μ g/mL. On the other hand, the same study found that Khaya grandifoliola's volatile extract showed a high level of cytotoxicity against MCF7 cells, with an IC 50 of 21.8 μ g/mL.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…These extracts are therefore considered non-toxic. Similar research by EL Souda et al [ 42 ] showed that the volatile extract of Khaya senegalensis had moderate cytotoxicity on MCF7 cells with a IC 50 of 79.7 μ g/mL. On the other hand, the same study found that Khaya grandifoliola's volatile extract showed a high level of cytotoxicity against MCF7 cells, with an IC 50 of 21.8 μ g/mL.…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, the same study found that Khaya grandifoliola's volatile extract showed a high level of cytotoxicity against MCF7 cells, with an IC 50 of 21.8 μ g/mL. [ 42 ]. This would be supported by the high concentration of sesquiterpenes, particularly isocaryophyllene and humulene (caryophyllene), in the volatile extract of K. grandifoliola , which could be influenced by both the plant's collection site(region) and the parts of the plant used to prepare the extract.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 1,1,4,8-tetramethyl- cis -4,7,10-cycloundecatriene ( 244 ) from the flowers of the neem tree has been investigated [ 146 ]. The caryophyllene derivative iso-caryophyllene ( 253 ), E -caryophyllene ( 254 ), and caryophyllenyl alcohol ( 256 ) were found to be minor compounds from Cedrela odorata , Toona sinensis , and Kaya grandifoliola , respectively [ 133 , 135 , 138 ]. Himachalane-type sesquiterpenoids α -himachalane ( 257 ) were produced by three species, including Aglaia odorata , Azadirachta indica A. Juss, and Cedrela odorata , while β -himachalene ( 258 ) was produced by the leaves of Cipadessa baccifera [ 131 , 136 , 144 , 146 ].…”
Section: Phytochemistrymentioning
confidence: 99%
“…In addition, α -guaiene ( 262 ) was investigated from leaves of Toona sinensis and Cedrela odorata [ 125 , 136 ], and β -guaiene ( 263 ) was determined from Toona sinensis and Toona ciliata [ 125 , 143 ]. Cis -4(14),5-Muuroladiene ( 273 ), a muurolane-hydrocarbon type sesquiterpenoid, was recognized in several species, including Cedrela odorata , Cedrela fissilis , Swietenia macrophylla , and Kaya grandifoliola [ 133 , 136 , 154 ]. Moreover, cis -muurol-5-en-4- β -ol ( 274 ) was also found in the flower of Kaya grandifoliola [ 133 ].…”
Section: Phytochemistrymentioning
confidence: 99%
See 1 more Smart Citation